2015
DOI: 10.1111/gcb.12979
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying above‐ and belowground biomass carbon loss with forest conversion in tropical lowlands of Sumatra (Indonesia)

Abstract: Natural forests in South-East Asia have been extensively converted into other land-use systems in the past decades and still show high deforestation rates. Historically, lowland forests have been converted into rubber forests, but more recently, the dominant conversion is into oil palm plantations. While it is expected that the large-scale conversion has strong effects on the carbon cycle, detailed studies quantifying carbon pools and total net primary production (NPPtotal ) in above- and belowground tree biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
207
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 179 publications
(222 citation statements)
references
References 99 publications
(156 reference statements)
11
207
4
Order By: Relevance
“…Pregitzer & Euskirchen (2004) reported that the mean C pool of woody debris across tropical forests amounted to 10% of the total carbon stocks. Dead wood contributed 2.3% of total aboveground C stocks in the natural forest and 1.9% of that in the jungle rubber (Kotowska et al 2015). These values were five times lower compared to 33% of the C stock in Costa Rican natural forests (Clark et al 2002).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Pregitzer & Euskirchen (2004) reported that the mean C pool of woody debris across tropical forests amounted to 10% of the total carbon stocks. Dead wood contributed 2.3% of total aboveground C stocks in the natural forest and 1.9% of that in the jungle rubber (Kotowska et al 2015). These values were five times lower compared to 33% of the C stock in Costa Rican natural forests (Clark et al 2002).…”
Section: Discussionmentioning
confidence: 87%
“…In the natural forest total aboveground tree biomass (AGB) was more than two times higher and aboveground net primary productivity (NP-P wood ) was also higher than in the jungle rubber systems (Kotowska et al 2015). The high AGB and NPP wood in the natural forest could have one reason for the higher dead wood mass, bearing on its capacity to store stocks of C and N. The larger mean diameter and height of living trees in the aboveground structure of the natural forest provided evidence for a higher dead wood biomass (Kotowska et al 2015). As a result, jungle rubber systems apparently lack large dead wood pieces which is more of a structural characteristic of natural forests.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations